Psychological Safety in the EFL Classroom: Teaming up with WTC, Language Anxiety, Learning Experience, Motivation and Teacher Leadership - Kaila, Tuula (My University, 2020)
This thesis set out to explore the concept of psychological safety, originating from organisational studies, as a potentially useful new concept in (foreign) second language acquisition. First the concept is explored in relation to other, established concepts in the field: Willingness to Communicate (WTC), Foreign Language Anxiety (FLA), Motivation and Learning Experience as well as the three Teacher Leadership-factors of Responsiveness, Demandingness and Coercive Control. The concepts are then formulated into teacher and student questionnaires. 333 students and 7 teachers participated in the study in spring 2019. The different concepts and their relations were examined quantitatively through means, correlations and multiple regression analysis and the few open questions were content analysed to find themes from the student perspective. The results of the theoretical explorations showed that psycholocigal safety is partly present in the current concepts and could be a viable factor for consideration expecially for WTC and Learning Experience. Psychological safety could, furthermore, help conceptualise the relevant parts of context, a rising theme in SLA. The quantitative results showed a linear connection between psychological safety and WTC and significant correlations to other factors. Qualitative results showed that students value familiarity, acceptance and equal participation-all issues that are not presented well in the current concepts but are at the core of psychological safety. It is concluded that psychological safety could be a viable new concept for foreign language learning studies and that further exploration in relation to especially the concepts of WTC and learning experience could be fruitful.
Keywords: Psychological safety, motivation, language learning experience, willingness to communicate, language anxiety, language enjoyment, context, group dynamics, group cohesion, group norms, teacher leadership